Kancionál český M.V. Šteyera - návrh českého hymnografického kánonu [1] - Škarpová, Marie, 1977-; Hashemi, Michaela, 1958-; Masarykova univerzita. Ústav české literatury a knihovnictví (2006)
Analýza pozice Kancionálu českého M.V. Šteyera v českém literárním životě raného novověku naznačila, že tento zpěvník byl významnou součástí rekatolizační cenzury v pobělohorských českých zemích - měl být náhradou za "kacířské" (tj. nekatolické) zpěvníky, měl podat "správný" (tj. katolicky profilovaný) repertoár i jeho "správný" způsob četby. V práci se pokoušíme tento návrh českého (materiálního i výkladového) hymnografického kánonu 2. poloviny 17. století analyzovat
The analysis of the M. V. Šteyer Bohemian Hymn-book and its role in the Bohemian literary milieu of the Early Modern Age has suggested that, at the time, the hymn-book formed an important part of the catholizing censorship in the lands of Bohemia after 1620. The hymn-book was designed to replace the "heretic" (or non-catholic) hymnals and to comprise the "proper" (or Catholic-defined) corpus of selected songs while, simultaneously, it was also there to provide the readers with the "correct" ways of interpreting the songs. This project constitutes an attempt at analyzing the design of Bohemian (both material and explanatory) hymnographic canon of the second half of the 17th century
Vedoucí práce: Michaela Soleiman pour Hashemi
Dizertace (Ph.D.)--Masarykova univerzita, Filozofická fakulta, 2006
Keywords: disertace; disertations